ANALISIS BUSINESS CANVAS MODEL POTENSI WISATA EDUKASI KAMPUS SEBAGAI DAYA TARIK WISATA EDUKASI (Studi Kasus Sekolah Vokasi Institut Pertanian Bogor, Bogor, Jawa Barat): Business Canvas Model Analysis of University Potential as Educational Tourism Attraction (Case Study Vocational College of IPB University, Bogor, Jawa Barat) - Natasha Indah Rahmani; Kania Sofiantina Rahayu (IPB University, 2022)
Educational tourism is a branch of tourism that combines recreation with learning. Several campuses in the world have implemented educational tourism that takes place on campus and other public places that has the purpose to increase the regional income of an area as well as recreation for the tourist. To be able to make the Vocational School campus a tourist spot, it is necessary to create a business process that can explain how the tourism program will be run in a sustainable manner. The primary data collection method in the form of interviews was conducted with related actors and then analyzed using the 6A tourism component method, stakeholder analysis, and analysis. BMC (Business Model Canvas). Several related actors involved in this program involve various kinds of collaboration, both from the vocational school and from the government and private sectors. Starting from the Lecturer Team and the Deputy Dean of Infrastructure who has strong influence and interest because they are directly involved in managing tourist sites and making tourism programs for the Department of Transportation and the Hospitality Industry which has an important role but does not have much power in this program. ABSTRAKWisata Edukasi merupakan salah satu cabang dalam kepariwisataan yang menggambukan rekreasi dengan pembelajaran. Beberapa kampus di dunia memiliki kegiatan wisata edukasi yang bertempat di kampus maupun tempat-tempat publik lainnya yang bertujuan untuk meningkatkan pendapatan sebuah daerah sekaligus berekreasi. Untuk dapat membuat kampus Sekolah Vokasi menjadi tempat wisata, perlu dibuat proses bisnis yang bisa menjelaskan bagaimana program wisata akan dijalankan secara berkelanjutan. Metode pengambilan data primer berupa wawancara dilakukan kepada aktor terkait dan selanjutnya dianalisis dengan metode metoda komponen pariwisata 6A, stakeholder analysis dan analisis. BMC (Business Model Canvas). Beberapa aktor terkait yang terlibat pada program ini melibatkan berbagai macam kolaborasi baik dari pihak sekolah vokasi maupun dari sisi pemerintahan dan sektor privat. Mulai dari Tim Dosen dan Wakil Dekan Sarana Prasarana yang memiliki Pengaruh dan Kepentingan tinggi karena terlibat langsung dalam pengelolaan lokasi wisata dan pembuatan program wisata hingga ada Dinas Perhubungan dan Industri Perhotelah yang memiliki peran penting tapi tidak terlalu memiliki kekuatan dalam program ini.